A Smart Photosensitizer–Manganese Dioxide Nanosystem for Enhanced Photodynamic Therapy by Reducing Glutathione Levels in Cancer Cells. (24th March 2016) - Fan, Huanhuan; Yan, Guobei; Zhao, Zilong; Hu, Xiaoxiao; Zhang, Wenhan; Liu, Hui; Fu, Xiaoyi; Fu, Ting; Zhang, Xiao‐Bing; Tan, Weihong
Abstract: Photodynamic therapy (PDT) has been applied in cancer treatment by utilizing reactive oxygen species to kill cancer cells. However, a high concentration of glutathione (GSH) is present in cancer cells and can consume reactive oxygen species. To address this problem, we report the development of a photosensitizer–MnO2 nanosystem for highly efficient PDT. In our design, MnO2 nanosheets adsorb photosensitizer chlorin e6 (Ce6), protect it from self‐destruction upon light irradiation, and efficiently deliver it into cells. The nanosystem also inhibits extracellular singlet oxygen generation by Ce6, leading to fewer side effects. Once endocytosed, the MnO2 nanosheets are reduced by intracellular GSH. As a result, the nanosystem is disintegrated, simultaneously releasing Ce6 and decreasing the level of GSH for highly efficient PDT. Moreover, fluorescence recovery, accompanied by the dissolution of MnO2 nanosheets, can provide a fluorescence signal for monitoring the efficacy of delivery. Abstract : Ein Photosensibilisator‐MnO2 ‐Nanosystem für die hocheffiziente photodynamische Therapie wurde entwickelt. Das Nanosystem kann mit intrazellulärem Glutathion (GSH) reagieren, wobei das GSH‐Niveau verringert und der Photosensibilisator vollständig freigesetzt wird, was die therapeutische Effizienz verbessert.